2020
DOI: 10.1002/mma.6416
|View full text |Cite
|
Sign up to set email alerts
|

A novel model of nonlocal thermoelasticity with time derivatives of higher order

Abstract: The objective of this work is to introduce a new system of differential equations describing the nonlocal thermoelasticity theory with higher time derivatives and two-phase lags. In order to obtain this model, we used the nonlocal continuum theory proposed by Eringen and the methodology of the Taylor series expansion of higher-order time derivatives. Some generalized thermoelasticity theories follow as limited cases. This model is used to study the thermoelastic interaction in a nonlocal medium. The medium is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(20 citation statements)
references
References 52 publications
(69 reference statements)
3
16
0
1
Order By: Relevance
“…The reported findings and conclusions are consistent with those of various literature researchers [52].…”
Section: Resultssupporting
confidence: 92%
“…The reported findings and conclusions are consistent with those of various literature researchers [52].…”
Section: Resultssupporting
confidence: 92%
“…Numerical results are now presented to explain the variation of displacement u, temperature θ , the strain e and the non-local thermal stress τ x x as well as discussed on the obtained results. In order to find the solutions for physical field in space-time areas, we must apply a technique of inversion approximation (40) proposed by Zakian [16,48] to equations ( 34), ( 35), ( 38) and ( 39), respectively. For all numerical calculations, Mathematica programming Language is employed.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Green and Naghdi presented a new generalized thermoelastic theory on the basis of Fourier's law [10][11][12], their theory was proposed in three separate models, the first and second theories are called GN-I and GN-II, respectively, and the third one is called GN-III. Relying on higher-order time derivatives, Abouelregal [13][14][15][16][17][18] did some investigation in order to alter the conventional Fourier's law. In recent years, many researchers have been attracted to examine the Moore-Gibson-Thompson equation (MGT) as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the experimental observations of micro-/nano-scale structures, it is shown that mechanical properties depend on the size, and these properties cannot be seen when we use the classical theories of elasticity [8][9][10][11] . Hence, modified elasticity theories such as the MCS, the nonlocal continuum mechanics, the nonlocal strain gradient theory, and the strain gradient theory are widely used to analyze the dynamic and static responses of micro-/nano-scale structures [12] .…”
Section: Introductionmentioning
confidence: 99%